Environmental and thermal aging studies on plastics and biopolymers : changes in mechanical properties and emissions of volatile organic compounds (VOCs) - Jacob John, Maya (University of Pretoria, 2025)
Dissertation (MSc (Chemical Technology))--University of Pretoria, 2024.